2009
DOI: 10.1055/s-0029-1186069
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Treatment of Carvedilol Following Low Dose Landiolol has Preventive Effect for Atrial Fibrillation after Coronary Artery Bypass Grafting

Abstract: Postoperative treatment with carvedilol following landiolol has the effect of preventing tachycardia during AF after coronary artery bypass grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…The sample size of these studies ranged from 53 to 207 (total 765). Four studies in this meta-analysis enrolled patients undergoing coronary artery bypass grafting (CABG) only [15][18]. The remaining two included patients undergoing CABG and/or valve surgery [14], [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size of these studies ranged from 53 to 207 (total 765). Four studies in this meta-analysis enrolled patients undergoing coronary artery bypass grafting (CABG) only [15][18]. The remaining two included patients undergoing CABG and/or valve surgery [14], [19].…”
Section: Resultsmentioning
confidence: 99%
“…Carvedilol was administered orally by different regimens and formulations. Timing of initiation for carvedilol prophylaxis was 3–10 days before the surgery in the preoperative prophylaxis studies [15], [16], [19] and within 24 hours of surgery in the postoperative group [17], [18]. Definition of POAF in terms of duration varied among the studies.…”
Section: Resultsmentioning
confidence: 99%
“…Landiolol was not assessed in our study; but in other studies, landiolol has demonstrated an enhanced protective effect against tachycardia during AF in post-CABG patients. 11 Another study demonstrated that in post-CABG patients, therapeutic landiolol in ''low doses'' can decrease the prevalence of AF. 12 However, our study did not demonstrate any difference regarding the incidence or prevalence of arrhythmias or postoperative 6-month mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The utility of landiolol for preventing postoperative AF has been reported widely, [6][7][8] but this is the fi rst prospective randomized trial of postoperative landiolol and the dose (0.5 to 2 μg/kg/min) is the lowest for postoperative prophylactic administration. The ideal approach is to prevent postoperative AF without worsening hemodynamics, and this was achieved with ultra-low dose landiolol administration in this study.…”
Section: Discussionmentioning
confidence: 99%